2012
DOI: 10.2337/dc12-0463
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Heart Rate Variability Among Youth With Type 1 Diabetes

Abstract: OBJECTIVEThis study compared heart rate variability (HRV) parameters in youth with and without type 1 diabetes and explored potential contributors of altered HRV.RESEARCH DESIGN AND METHODSHRV parameters were measured among 354 youth with type 1 diabetes (mean age 18.8 years, diabetes duration 9.8 years, and mean A1C 8.9%) and 176 youth without diabetes (mean age 19.2 years) participating in the SEARCH CVD study. Multiple linear regression was used to assess the relationship between diabetes status and HRV par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
83
3
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 33 publications
14
83
3
5
Order By: Relevance
“…This is the first large-scale study examining heart rate variability in relation to risk of nephropathy in adolescents with type 1 diabetes who have not yet developed microalbuminuria. Reduced heart rate variability has been associated with microalbuminuria in older adolescents (4,9). In the SEARCH for Diabetes in Youth Study, lower SDNN (one measure of overall heart rate variability) was associated with microalbuminuria in older adolescents with type 1 diabetes (mean age 18.8 years, mean duration 9.8 years) (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first large-scale study examining heart rate variability in relation to risk of nephropathy in adolescents with type 1 diabetes who have not yet developed microalbuminuria. Reduced heart rate variability has been associated with microalbuminuria in older adolescents (4,9). In the SEARCH for Diabetes in Youth Study, lower SDNN (one measure of overall heart rate variability) was associated with microalbuminuria in older adolescents with type 1 diabetes (mean age 18.8 years, mean duration 9.8 years) (9).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced heart rate variability has been associated with microalbuminuria in older adolescents (4,9). In the SEARCH for Diabetes in Youth Study, lower SDNN (one measure of overall heart rate variability) was associated with microalbuminuria in older adolescents with type 1 diabetes (mean age 18.8 years, mean duration 9.8 years) (9). In this current study, we found significantly lower SDNN and RMSSD (measures of overall heart rate variability) and faster heart rate in younger adolescents at risk for nephropathy (mean age 14.1 years, mean duration 6.4 years).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…131 However, 1 large study (n=354) found overall heart rate variability reduction, suggesting a more advanced state of cardiac autonomic neuropathy. 132 Predictors of abnormal heart rate variability in children with T1DM included higher HbA 1c 132 and low PA. 133 The few small studies of neurological function conducted in youth with T2DM showed lower cognitive function, 134 peripheral neuropathy, 135 and lower heart rate variability compared with control subjects. 136 These early changes in neurological function have implications for future CVD because autonomic dysfunction measured in childhood predicts increased arterial stiffness 18 years later.…”
Section: Maahs Et Al Cvd Risk Factors In Youth With Diabetes Mellitusmentioning
confidence: 99%
“…Other studies have also demonstrated higher resting heart rates 16 and lower heart rate variability in patients with T1DM compared with controls. 17 However, heart rate and heart rate variability are influenced by many different inputs including parasympathetic tone, hormones, temperature, and levels of various ions and molecules. The lack of a difference in the norepinephrine analog tracer in the myocardium between the normal subjects and the patients with T1DM may simply mean that sympathetic stimuli/hormones are not the main influence on the heart rate difference between the 2 groups.…”
mentioning
confidence: 99%